Evaluating customer satisfaction and service quality using servqual model in the Courier Service Delivery (CSD) provider (Pilot study: Surabaya city, Indonesia) - H Al Rosyid; E Setijadi; S M S Nugroho (IPTEK Journal of Proceedings Series, 2018)
In the last decade, the number of Courier Service Delivery (CSD) Providers has been increasing and growing rapidly, it certainly makes the characteristics of each providers more diverse as well. The Government who serve as assessors who are follow-up of monitoring and evaluation results, often find many problems in the selection of variables used as aspects of assessment. One important aspect in figuring out valuation is the value of customer satisfaction. This study aims to measure and evaluate the Customer Satisfaction Index (CSI) modification with the use of service qualities dimension or known as SERVQUAL model. Not only that, this paper also examines the influence of five dimensions on the model to the customer satisfaction using Ordinary Least Square (OLS) regression method. The dimensions are Tangible, Reliability, Responsiveness, Assurance, and Empathy. This research was conducted on a total of 249 respondents in 6 sample providers. According to the results obtained that CSI scores in the range of 80.27 to 84.76 (good and very good) and the dimensions of service quality that significantly affect on customer satisfaction were Tangible and Responsiveness